Dental Carries Prevalence and Associated Factors of Secondary Level Students in Eastern Nepal - Bhujel, Kajol; Poudyal, Jiwan Kumar; Parajuli, Sumitra; Gaire, Pratikshya; Upadhyay, Hari Prasad (International Journal of Silkroad Institute of Research and Training, 2024)
Background: Dental caries or a tooth decay is a common oral health condition characterized by demineralization oftooth enamel and subsequent formation of cavities It is a global public health problem and influence the overall health ofchildren.Method: A cross-sectional study was conducted among 343 secondary level school students by complete enumerationsampling method. A pretested, standardized, closed-ended questionnaire and a standard Decayed, Missing, and Filledprimary Teeth (DMFT) tools were adopted to find out the prevalence and associated factors of Dental Caries. Face to faceinterview and oral assessment under natural day light were uses for data collection methods. Data were coded, entered,cleaned and analyzed by using SPSS version 22. Descriptive and bi-variate statistics were employed to test the associationbetween dependent and independent variables. P-value less than 0.05 was taken as significant association and result waspresented in text, tables and graph.Result: The overall prevalence of dental caries was 68.5% with a mean and SD of DMFT of 1.53±1.462 and femalestudents were most sufferer (70.1%) from dental caries. There was a significant association of dental caries with mother’seducational status (p=0.009), consumption of sugary tea/coffee (p=